Pinjaman Keuangan: Analisis Akad Pembiayaan Multiguna dengan Agunan SK PNS di Bank Aceh Syariah - Junaidi, Junaidi (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2023)
Financial loans provided by banks to Civil Servants (Pegawai Negeri Sipil) are one of the banking products offered by both conventional and Islamic banks. Bank Aceh Syariah, in meeting the needs of these loans, offers a financial product with a murabahah scheme (profit-sharing) but with the condition that the PNS appointment letter serves as collateral. Therefore, this article aims to explore and analyze the contract used in financial loans with the appointment letter as collateral. The research method used in this study is qualitative and descriptive, with two sources of data: primary data and secondary data. Primary data was obtained from interviews with three customers of Bank Aceh Syariah Capem Rimo Gunung Meriah Aceh Singkil, while secondary data was obtained from books, journal articles, and relevant internet sources. The findings of this study reveal that financing undertaken by Civil Servants at Islamic Financial Institutions (Lelmbaga Keuangan Syariah) is a common practice, and Bank Aceh Syariah has provided access with various contracts, namely murabahah, ijarah, and musyarakah mutanaqisah. The practice followed at Bank Aceh Syariah Capem Rimo Gunung Meriah Aceh Singkil requires the appointment letter as collateral (marhun). According to the fiqh book as a basis for reference in Islamic Financial Institutions (LKS), collateral must be in the form of goods or negotiable instruments that can be traded. Therefore, from this perspective, an appointment letter cannot be considered as collateral (marhun).